Uso de los residuos de la cáscara de banano (Musa paradisiaca), para la elaboración de material plástico biodegradable, ESPAM MFL - García Loor, Cinthia Viviana (2021)
The present research aimed to determine the use of banana peel residues (Musa paradisiaca), for the production of biodegradable plastic, in order to evaluate the total use of the raw material and determine its degradation time. Banana peel, H2O (water), Na2S2O5 (sodium metabisulfite) to prevent enzymatic browning, HCl (hydrochloric acid), NaOH (sodium hydroxide) and glycerin as plasticizers for the formation of the bioplastic according to the methodology of López et al., (2014) were used for the production of biodegradable sheets, obtaining a yield of 8.09% of the sample. Once the biodegradable plastic was obtained, a prototype of bags with dimensions of 225 cm2 (15x15) cm was made, and then carry out the verification tests of the estimated degradation time of 30 days through daily qualitative observation, the prototype bags subjected to the outdoor degradability method were completely degraded after 12 days; By the water degradability method at 9 days and by composting at 5 days, obtaining a degradation efficiency of 100% higher than the hypothesis, the method that was closest to the estimated time was the outdoor technique. In the valuation of biodegradable bags it is determined that it is not a very promising line of work due to its high cost and it is not affordable for all public, the value of 4 biodegradable bags was $ 1.63 225 cm2 (15x15) cm, which estimates that if a large-scale production is carried out, the calculated sale price decreases in the established valuation.